2021
DOI: 10.22541/au.162524921.19356960/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characteristics and Outcomes of Ventricular Tachycardia and Premature Ventricular Contractions Ablation in Patients with Prior Mitral Valve Surgery

Abstract: Background: Data regarding ventricular tachycardia (VT) or premature ventricular complex (PVC) ablation following MVS is limited.) CA can be challenging given perivalvular substrate in the setting of mitral annuloplasty or prosthetic valves. Objective: To investigate the characteristics, safety, and outcomes of radiofrequency catheter ablation (CA) in patients with prior mitral valve surgery (MVS) and ventricular arrhythmias (VA). Methods: We identified consecutive patients with prior MVS who underwent CA for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…">We did compare patients with coronary artery disease (CAD) to patients without CAD. As discussed in our manuscript, MVS patients with a history of CAD showed a trend of better VA recurrence‐free survival compared with those without CAD history 1 …”
Section: Responsementioning
confidence: 59%
See 2 more Smart Citations
“…">We did compare patients with coronary artery disease (CAD) to patients without CAD. As discussed in our manuscript, MVS patients with a history of CAD showed a trend of better VA recurrence‐free survival compared with those without CAD history 1 …”
Section: Responsementioning
confidence: 59%
“…However, our cohort is one of the least heterogeneous in the literature addressing VAs ablation in patients MVS as most prior studies evaluated arrhythmias in patients with heart surgery or valve surgery in general as discussed in the introduction section of our manuscript. 1 Although mitral regurgitation is classified into primary and secondary as proposed by the American College of Cardiology and the American Heart Association (ACC/AHA) guidelines, different classifications and subgroups exist based on causes, mechanisms, and leaflet motion, which might cause confusion due to overlapping terminologies. 2,3 We concur that the study of VA outcomes based on the specific mechanism of mitral disease would be a welcome addition to the literature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Complications in this study were related to vascular access, with one femoral artery pseudoaneurysm requiring surgical repair, and one common iliac dissection conservatively managed. More recently, Khalil et al (2021) reported a case series of 31 patients with prior MVR undergoing ablation for VT ( n = 16) orpremature ventricular complex ( n = 15) 6 . Of the patients undergoing VT ablation, 4 had MVR and 12 had mitral valve repair.…”
Section: Study N Average Age Valve Intervention Focus Of Vt Involving...mentioning
confidence: 99%
“…3 Previous studies have provided some insights into the mechanisms of VT in the specific population of patients with previous valve interventions. [4][5][6] Overall, they show that the presence of voltage abnormalities and abnormal electrograms with perivalvular distribution is almost a universal finding, but these regions of fibrosis are not always responsible for the clinical VTs, which can instead be related to ischemic scars or other nonischemic processes. Although intramyocardial reentry is the predominant mechanism in these patients, bundle branch reentry has been reported in up to 10% of cases, and focal arrhythmias can also be encountered.…”
mentioning
confidence: 99%